Meus hic ratibus qui pascitur ignis (VAL.FLAC.2.658), o Cízico: un Héctor frustrado - Río Torres-murciano, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
In the episode of Cyzicus, Valerius Flaccus problematizes the insertion into the epic poem of a tragic adventure, an erroneous night war between allies that, by means of hybris, confusion and subsequent recognition, takes the implied ones to the catastrophe. For this purpose, the author uses as fundamental trope tragic irony, as far as he sets the reader’s privileged knowledge of the story of the Argonauts against the ignorance of the prominent characters, whose heroic expectations will be frustrated. This way, the king who welcomes Jason dreams of personifying the Hector of the la Iliad, whereas the learned reader knows that he has to perform to the end the unsuccessful Cyzicus of the argonautic tradition.